Implementation of Electrical Equipment Control and Security System integrated with Internet of Things - Suprianto; Lestari, Meidi Wani; Frianto, Herri Trisna; Toruan, Henry H. Lumban; Zarina, Raja Intan binti Raja Zaki Hashim (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
Research on Electrical Equipment Security and Control Systems Using the Internet of Things aims to implement an IoT system for controlling electrical equipment and security systems. The owner of the security location will receive a phone call if an object is detected and can monitor and activate the alarm system while controlling electrical equipment. In addition to saving electricity, it is also intended that the detected object/human will change his mind. This system can be used anytime and anywhere. The specific target achieved is to implement a building security system and control electrical equipment using the internet of things. The method used is the experimental method, namely collecting data from the results of measuring electrical quantities in the system. The equipment used is the SIM800L module, PZEM sensor, PIR module-8 sensor, RTC, PCF8574, shift register 74HC595, ESP 32, Triac, Optocoupler, buzzer, contactor, and other supporting equipment. The results of the study show that the ability of the PIR sensor to detect objects has a sensitivity that is not all the same even with the same type, the sensitivity of the PIR sensor is influenced by the condition of the internet network, the location of the detection room, the length of the pir sensor cable to the esp 32, and the speed of the response of the designed system. Controlling electrical loads using the blynk application with contactor equipment can work effectively if the internet network conditions are stable, the effectiveness of using optocouplers and triacs allows the contactor to receive input quickly and responsively. Keywords: IoT, ESP 32, security, alarm, sensor